League ranking mobility affects attendance: Evidence from European Soccer Leagues - Gyimesi, A. (Journal of Sports Economics, 2020)
Ranking mobility belongs to the indicators of dynamic long-term competitive balance, as it is based on season to season changes in league rankings. If the uncertainty of outcome hypothesis holds at the league level, ranking mobility might increase demand for league games. This assumption is tested by using panel regression models on data of 19 European domestic soccer leagues. Ranking mobility is found to significantly affect average stadium attendance per game, particularly if only the top 5 ranking positions are considered. Results suggest that the closeness of competition across seasons is more important for the fans than within a season.